Structural change in Japan : macroeconomic impact and policy challenges - Aghevli, Bijan B.; Bayoumi, Tamim A.; Meredith, Guy.; International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1998)
By shifting and destabilizing the underlying economic relationships and creating uncertainty, structural change complicates the task of policy analysis. This volume describes how the IMF is responding to these challenges and how outside experts assess this effort.
"This volume is based on a seminar on structural change in Japan held in early 1997 and chaired by the IMF's First Deputy Managing Director, Stanley Fischer"--P. 4 of cover.
Includes bibliographical references.
osc 31/08/2016
Loans
Keywords: Structural adjustment (Economic policy).; Foreign exchange rates; Balance of payments; Monetary policy; Fiscal policy; Japan